2007
DOI: 10.1055/s-2007-967744
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Edema

Abstract: Facial aesthetic surgeons are sometimes challenged by the predicament of diagnosing and managing patients with chronic eyelid edema. Herein we provide a brief review of some of the more common causes of pre- and postoperative eyelid edema, many of which have important systemic implications, and offer management suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Other studies of chronic eyelid edema in rosacea did not mention dermal granulomas. 5,6 In none of our cases was rosacea felt to be the primary underlying cause, either clinically or histopathologically.…”
mentioning
confidence: 67%
“…Other studies of chronic eyelid edema in rosacea did not mention dermal granulomas. 5,6 In none of our cases was rosacea felt to be the primary underlying cause, either clinically or histopathologically.…”
mentioning
confidence: 67%
“…Mononucleosis was excluded by infectiologist. Medication induced eyelid oedema was absent as well [13].…”
Section: Discussionmentioning
confidence: 97%
“…Recognising eyelid oedema can be in differential diagnosis with pre or postoperative oedema with systemic implications as allergies, Ocular rosacea, Melkersson Rosenthal Syndrome, Floppy Eyelid Sydrome, Cold urticaria, Lymphedema, eyelid-dependent Keratoconjunctivitis sicca, all of which were excluded in our case. C1-Esterase Inhibitor Deficiency-Type Angi oedema as one of the cases was not tested, according the age 57 years and pitting oedema the diagnosis was not evaluated [13]. Blepharochalsis, although very similar, it is a rare form of eyelid oedema which can be unilateral, with initial symptoms unset at an age of 11 years old non pitting oedema ending hypervascular and with hyperpigmentation [14] [15].…”
Section: Discussionmentioning
confidence: 99%
“…50 Acquired lymphedema is a common post-surgical cancer treatment side-effect shown in several animal studies. [51][52] Animal studies revealed that post-operatively, mice had higher HA accumulation following lymph-node removal. 51 This lymphedema was reduced following hyaluronidase treatment in animal studies and immunohistochemical analysis demonstrated that hyaluronidase could augment lymphangiogenesis in lymphedematous limbs.…”
Section: Surgical Usesmentioning
confidence: 99%